Du Transperceneige de Jacques Lob et Jean-Marc Rochette à Snowpiercer de Bong Joon-Ho : une inspiration mutuelle entre arts visuels dans le domaine de la science-fiction. - Suk Hee Joo (ReS Futurae)
The release of the movie Snowpiercer, directed by the Korean Bong Joon-Ho, occurs in 2013, about twenty years after the publication of the post-apocalyptic graphic novel Le Transperceneige, which was created by Jacques Lob and Jean-Marc Rochette. Rather than adaptating, it should be considered recreating the original work, as the change of medium implies a change in the way of telling the story. Although the movie’s plot and framework partly come from the original graphic novel, it also brings its own narrative and formal innovations, so that the new work becomes part of a series of narratives stemming from the same fictional world. Moreover, these different kinds of visual art are combined in the making of Bong Joon-Ho’s film, whose aesthetic influences Jean-Marc Rochette in turn and leads him to draw another volume of the graphic novel after it. From Le Transperceneige to Snowpiercer, the story of the work deals non only with cultural transfer (from french to korean culture) or with mediatic transfer (from graphic novel to cinema), it deals above all with collective creation drawing from a shared fictional material.